Consumer Behavior Analysis at The de' Akur Rantauprapat Coffee Store - Wika Juliani Hasibuan; Pristiyono Pristiyono; Yuniman Zebua (PT Mattawang Mediatama Solution, 2022)
Hanging out in a coffee shop for some consumers has become a necessity that is difficult to avoid. Hanging out is an interesting part of consumer behavior to study through marketing mix and hedonism. So the purpose of this research is to reveal the factors that influence consumer behavior and to find out which variables have the most dominant influence on consumer behavior. Quantitative descriptive research approach, the sample is determined based on the number of indicators as much as 1 5 x 10 = 1 5 0 samples and the author sets it to be 200 samples. The sampling technique used is simple random sampling. The data analysis technique used in this research is Smart PLS v 3.0 to predict the relationship between one construct and another. Based on the respondent's profile by gender, it is dominated by men, with the age above 31 years and the highest education being high school or equivalent, bachelor's and master's degree. The results of hypothesis testing, it shows that there is theoretical and scientific support that the marketing mix and hedonism variables and their indicators are very significant in influencing consumer behavior. The hedonism variable is the most dominant variable in influencing consumer behavior